Представьте в виде многочлена:

1) -(√3-х)(х^2-3)(х+√3)
2) (х^2-√5)^2

Mariecharlaii Mariecharlaii    3   09.12.2021 07:36    0

Ответы
nata1316 nata1316  27.01.2022 17:53

x^{4}-6x^{2}+9 \ ;

x^{4}-2x^{2}\sqrt{5}+5 \ ;

Пошаговое объяснение:

1) \ -(\sqrt{3}-x)(x^{2}-3)(x+\sqrt{3})=(-(\sqrt{3}-x))(x+\sqrt{3})(x^{2}-3)=(-\sqrt{3}+x) \cdot

\cdot (x+\sqrt{3})(x^{2}-3)=(x-\sqrt{3})(x+\sqrt{3})(x^{2}-3)=(x^{2}-(\sqrt{3})^{2})(x^{2}-3)=

=(x^{2}-3)(x^{2}-3)=(x^{2}-3)^{2}=(x^{2})^{2}-2 \cdot x^{2} \cdot 3+3^{2}=x^{2 \cdot 2}-6x^{2}+9=

=x^{4}-6x^{2}+9;

2) \ (x^{2}-\sqrt{5})^{2}=(x^{2})^{2}-2 \cdot x^{2} \cdot \sqrt{5}+(\sqrt{5})^{2}=x^{2 \cdot 2}-2x^{2}\sqrt{5}+5=x^{4}-2x^{2}\sqrt{5}+5;

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика